Development of Fiber-Reinforced Concrete for Road Pavement Surfaces Enhanced with Complex Additives - Karapetyan, Amalia; Arzumanyan, Avetik; Muradyan, Nelli; Grigoryan, Artyom; Egnatosyan, Siranush; Egnatosyan, Naira; Badalyan, Maria (Civil Engineering Journal, 2026)
This study aims to develop high-performance road pavement concrete capable of withstanding increasing traffic loads while ensuring long service life and reduced maintenance needs. The research focuses on enhancing the mechanical characteristics of fine-grained concrete used in the outer pavement layer through the incorporation of complex additives and dispersed reinforcement. The methodology involved modifying the concrete matrix using the superplasticizer Melflux 5581F, microsilica MK-85, and varying percentages of basalt fibers introduced through different preparation techniques. Mechanical testing, including compressive and flexural strength evaluations, was performed on 40×40×160 mm specimens cured under standard conditions and tested at 7 and 28 days. The analysis showed that Melflux 5581F significantly enhanced strength without increasing cement content, while MK-85 further improved compressive and flexural strengths by up to 50.59% and 46.28%, respectively. The addition of basalt fibers increased flexural strength, with optimal formulations achieving 89.49 MPa in compressive strength and 11.14 MPa in flexural strength. These findings demonstrate that the combined use of chemical, mineral, and fiber additives, together with appropriate technological approaches, substantially improves the performance of road concrete. The proposed modified concrete exhibits enhanced durability, offering a promising solution for extending pavement service life and reducing repair frequency.